(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
A training and assistance activity was conducted on processing kimpul tubers for homemakers and the Youth Organization of Cukilan Village, Semarang Regency. This initiative was based on the needs of the local community, where kimpul tubers are abundant but minimally processed. The limited processing of kimpul tubers is not only due to a lack of knowledge about proper processing techniques but also because of low community interest in exploring their potential as a food product. To address this issue, homemakers and youth organization members were targeted as participants because they typically have more time at home and greater opportunities to learn compared to adult men who are primarily engaged in farming. This community service aimed to equip them with practical skills for processing kimpul tubers into flour and creating various food products using the produced kimpul flour. The activity employed an adult learning approach, where participants played an active role in every stage of the program. The implementation consisted of three main stages: counseling, training, and assistance in processing kimpul tubers into flour, followed by demonstrations of creating food products based on kimpul flour. The results of this community service showed a 100% increase in the knowledge and skills of participants related to processing kimpul tubers and creating kimpul-based food products. Therefore, it can be concluded that this activity successfully fulfilled its purpose as a community service initiative. — Telah dilakukan suatu kegiatan pelatihan dan pendampingan pengolahan umbi kimpul untuk ibu-ibu rumah tangga dan Karang Taruna Desa Cukilan Kabupaten Semarang. Pelatihan dan pendampingan pengolahan umbi kimpul ini didasarkan pada kebutuhan masyarakat setempat, dimana populasi umbi kimpul cukup banyak namun pengolahan umbi kimpul masih sangat terbatas. Keterbatasan pengolahan umbi kimpul ini selain disebabkan oleh masih kurangnya pengetahuan pengolahan umbi kimpul yang baik, juga disebabkan rendahnya minat masyarakat dalam mengeksplor potensi pemanfaatan umbi kimpul untuk produk pangan. Untuk itu perlu pelibatan dari ibu rumah tangga dan karang taruna sebagai subyek yang memiliki lebih banyak waktu di rumah (kesempatan belajar lebih banyak) dibanding warga dewasa pria yang bertani. Tujuan pengabdian masyarakat ini adalah untuk meningkatkan pengetahuan/ keterampilan khalayak sasaran dalam membuat tepung kimpul dan produk pangan berbasis tepung kimpul. Metode pengabdian menggunakan metode pembelajaran orang dewasa yaitu partisipan berperan aktif dalam setiap tahapan kegiatan ini. Terdapat tiga tahap dalam pelaksanaan kegiatan, yakni penyuluhan, pelatihan dan pendampingan pengolahan umbi kimpul menjadi tepung, dan demonstrasi pembuatan produk pangan berbasis tepung umbi kimpul. Hasil pengabdian masyarakat menunjukkan terdapat peningkatan 100% pengetahuan dan keterampilan peserta kegiatan terkait pengolahan umbi kimpul dan produk pangan berbasis kimpul. Dengan demikian dapat disimpulkan bahwa kegiatan ini telah sesuai dengan tujuan pengabdian masyarakat.